Segmental renal artery and popliteal artery embolism in an adult patient with rheumatic heart disease and atrial fibrillation: A case report. (2020) - Parajuli, Purushottam; Luitel, Bhoj Raj; Chapagain, Suman; Pradhan, Manish Man; Gnyawali, Diwas; Sigdel, Prem Raj; Pandit, Durga; Guragain, Bipin; Chudal, Sampanna; Verma, Rupesh; Poudyal, Sujeet; Chalise, Pawan Raj; et al.
Highlights: Atrial fibrillation is associated with peripheral embolism. Renal artery embolism is reported in rare instances. Clinical suspicion in high risk patient and urgent treatment is key to success. Abstract: Introduction: Renal artery embolism is uncommon cause of flank or back pain. Of all embolic episodes in patients with atrial fibrillation, 2–4% are renal artery embolism. Early thrombolysis within 90 min has favorable renal outcome. Long term anticoagulation can prevent recurrent embolic episodes. Two different embolic phenomenon within short span in same patient is not described in literature. Presentation of case: We describe fifty-year-old female with rheumatic heart disease with atrial fibrillation presented as renal segmental artery emboli with popliteal artery emboli within seven-day interval. Discussion: Embolic phenomenon is well known in atrial fibrillation. High index of suspicion in patient with risk factors of thromboembolism with appropriate use of contrast enhanced computed tomography can help early diagnosis. Renal artery embolism is managed with anticoagulation or thrombolysis based on duration of presentation. Peripheral artery embolism can be diagnosed with Doppler ultrasonography. Thrombus can be removed with endovascular procedure or open surgical technique. Holistic patient management includes cardiac workup and treatment of factors predisposing to embolization. Conclusion: Early identification and urgent treatment is key to the management of embolic episode in patient with atrial fibrillation. Long term prophylaxis can prevent further episodes.